PERIODONTAL DISEASE AND NOSOCOMIAL PNEUMONIA: A SYSTEMATIC REVIEW - Hanifa Salma, Yasmin (Journal of Health and Dental Sciences, 2024)
This study aims to comprehensively review the literature and assess periodontal disease as a risk factor for nosocomial pneumonia in hospitalized patients, particularly those receiving treatment in the intensive care unit (ICU). Case-control studies and "full texts" published between 2013 and 2023 were the data sources and literature following PRISA-ScR criteria. Online electronic search engines from databases, including PubMed, Cochrane Library, and Google Scholar, were used to conduct the scoping review. Four articles were obtained by carefully choosing papers based on inclusion and exclusion criteria. These were then tallied and examined. In this review, four of the 1741 publications were covered. In patients receiving hospital treatment, particularly in the intensive care unit, there is a strong correlation between periodontal disease and nosocomial pneumonia. DOI : 10.54052/jhds.v4n1.p81-90